Система електронного документообігу як засіб організації роботи установи - Мищишин, Віталій; Жежнич, Павло (Видавництво Львівської політехніки, 2012)
Electronic document – a document in which information is recorded in the form of electronic data, including the required information document. hese electronic documents are set by state agencies, local governments, enterprises, institutions and organizations of all forms of property in accordance with legislation of Ukraine. Advantages of electronic document management system are: centralized management, service level, version control, a new level of service, consolidation of data, increase productivity while reducing costs.
Keywords: електронний документ; система електронного документообігу; версійність; політика доступу